2016
DOI: 10.1136/jmedgenet-2015-103684
|View full text |Cite
|
Sign up to set email alerts
|

AKAP2identified as a novel gene mutated in a Chinese family with adolescent idiopathic scoliosis

Abstract: BackgroundAdolescent idiopathic scoliosis exhibits high heritability and is one of the most common spinal deformities found in adolescent populations. However, little is known about the disease-causing genes in families with adolescent idiopathic scoliosis exhibiting Mendelian inheritance.ObjectiveThe aim of this study was to identify the causative gene in a family with adolescent idiopathic scoliosis.MethodsWhole-exome sequencing was performed on this family to identify the candidate gene. Sanger sequencing w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 27 publications
0
37
0
Order By: Relevance
“…In addition, whole-exome sequencing (WES) of a Chinese AIS family identified a rare variant in the A-kinase anchor protein 2 gene (AKAP2; MIM# 604582) (Li et al, 2016). However, in both cases, the underlying pathogenic pathways remain unclear as little is known regarding the normal functions of the two affected genes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, whole-exome sequencing (WES) of a Chinese AIS family identified a rare variant in the A-kinase anchor protein 2 gene (AKAP2; MIM# 604582) (Li et al, 2016). However, in both cases, the underlying pathogenic pathways remain unclear as little is known regarding the normal functions of the two affected genes.…”
Section: Introductionmentioning
confidence: 99%
“…Based on genome-wide association study (GWAS) and other similar association studies, single nucleotide polymorphisms (SNPs) of several genes such as GPR126 (Kou et al, 2013;Liu et al, 2018), PAX1 (Sharma et al, 2015;Liu et al, 2019), LBX1 (Takahashi et al, 2011;Liu et al, 2017), and BNC2 (Ogura et al, 2015), were known to increase the risk of AIS. There was also evidence that rare mutations of some genes may be responsible for AIS, such as FBN1 (Buchan et al, 2014a), AKAP2 (Li et al, 2016) and MAPK7 (Gao et al, 2017). Other studies illustrated the association between CNV and AIS (Buchan et al, 2014b).…”
Section: Introductionmentioning
confidence: 98%
“…Although studies to discover the underlying mechanisms of AIS had been conducted for many years, the etiology is still unclear. Previous studies showed that genetic factors from single nucleotide variant (SNV) to copy number variants (CNV), played a pivotal role in the development of AIS (Kesling and Reinker, 1997;Li et al, 2016;Gao et al, 2017). Based on genome-wide association study (GWAS) and other similar association studies, single nucleotide polymorphisms (SNPs) of several genes such as GPR126 (Kou et al, 2013;Liu et al, 2018), PAX1 (Sharma et al, 2015;Liu et al, 2019), LBX1 (Takahashi et al, 2011;Liu et al, 2017), and BNC2 (Ogura et al, 2015), were known to increase the risk of AIS.…”
Section: Introductionmentioning
confidence: 99%
“…Library construction was performed by the customed Roche NimbleGen SeqCap EZ System (Roche, Madison, Wisconsin, USA), and 90-cycles Paired-end sequencing was conducted on Illumina HiSeq2500 Analyzers (Illumin, San Diego, California, USA). Read mapping and variant analysis procedures were as described previously (Li et al 2016b). On the basis of dbSNP database (www.ncbi.nlm.nih.gov/SNP/), Exome Variant Server database (http://evs.gs.washington.edu/EVS/), the Human Gene Mutation Database (http://www.hgmd.cf.ac.uk/ac/index.php) and 1,000 Genomes (http://browser.1000genomes.org/index.html) annotation, the high-frequency (minor allele frequency ≥ 0.01) polymorphism variations were excluded.…”
Section: Targeted Exome Sequencing and Mutation Predictionmentioning
confidence: 99%